Introduction to Hydro Energy Systems Basics, Technology and Operation - Wagner, Hermann-Josef.; Mathur, Jyotirmay; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The authors have tried to strike a balance between a short book chapter and a very detailed book for subject experts. There are three prime reasons behind for doing so: first, the field is quite interdisciplinary and requires simplified presentation for a person from non-parent discipline. The second reason for this short-version of a full book is that both the authors have seen students and technically oriented people, who were searching for this type of book on hydro energy. The third reason and motivation was considering engineers who are starting their career in hydro energy sector. This book is targeted to present a good starting background and basic understanding for such professionals.
Introduction and Status of Hydropower -- Terminology and Legal Framework -- Physical and Technical Basics of Hydropower -- Components of Hydropower Plants -- Hydraulic turbines: Types and operational aspects -- Use of Ocean Energies -- Economics of Hydropower Plants -- Outlook for Hydropower.
Keywords: Engineering; Mechanical engineering; Civil engineering; Computer engineering; Renewable energy sources; Engineering economy; Engineering; Renewable and Green Energy; Mechanical Engineering; Civil Engineering; Electrical Engineering; Energy Economics